Contesting the Equivalency of Continuous Sedation until Death and Physician-assisted Suicide/Euthanasia: A Commentary on LiPuma. Issue 5 (4th August 2015) - Raho, Joseph A.; Miccinesi, Guido
Abstract: Patients who are imminently dying sometimes experience symptoms refractory to traditional palliative interventions, and in rare cases, continuous sedation is offered. Samuel H. LiPuma, in a recent article in this Journal, argues that continuous sedation until death is equivalent to physician-assisted suicide/euthanasia based on a higher brain neocortical definition of death. We contest his position that continuous sedation involves killing and offer four objections to the equivalency thesis. First, sedation practices are proportional in a way that physician-assisted suicide/euthanasia is not. Second, continuous sedation may not entirely abolish consciousness. Third, LiPuma's particular version of higher brain neocortical death relies on an implausibly weak construal of irreversibility—a position that is especially problematic in the case of continuous sedation. Finally, we explain why continuous sedation until death is not functionally equivalent to neocortical death and, hence, physician-assisted suicide/euthanasia. Concluding remarks review the differences between these two end-of-life practices.